Shifts in Economic Geography and their Causes. - Venables, A (Centre for Economic Performance, LSE, 2006)
This paper analyses some of the forces that are changing the spatial distribution of activity inthe world economy. It draws on the 'new economic geography' literature to argue theimportance of increasing returns to scale and cumulative causation processes in shaping theproductivity and comparative advantage of different regions. In the presence of suchincreasing returns there may be persistent spatial disparities in productivity. Economicdevelopment will tend to be 'lumpy', with some regions (countries, or smaller areas such ascities) experiencing rapid growth and others being left behind.